An Intervention to Retrain Attributions Using CBT: A Pilot Study. (3rd April 2017) - Bosnjak, Amira; Boyle, Christopher; Chodkiewicz, Alicia R.
Abstract : The role of affective and cognitive factors in learning have long been recognised as imperative determinants of the learning process. Maladaptive styles with which we perceive and explain accomplishments and failures in achievement outcomes have an important motivational impact upon approach and avoidance behaviours towards academic tasks. Interventions to change these maladaptive styles are well established, although they stand to gain via addition of cognitive behavioural therapy components. A pilot study attribution retraining intervention was implemented with eight secondary school students, and their results on academic performance, self-concept, and attributional styles were compared to a control group. With significant gains in some specific academic domains, the attributional retraining program is being substantiated for effective use within secondary schools. Implications suggest that this could be an effective tool to retrain students' attributions, with some gains, as the reattribution technique is revisited and reinvigorated.